ANALISIS KESEIMBANGAN ENERGI DAERAH ISTIMEWA YOGYAKARTA - , EKO HARYONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Daerah Istimewa Yogyakarta (DIY) is one of the provinces in Indonesia that does not have a backup or potential sources of non-renewable primary energy. The non-renewable energy demand until this time such as oil and gas is supplied from the outside of region. DIY is in the interconnection systems of Jawa Madura Bali (JAMALI) and does not have the large-scale power system. DIY has renewable energy sources such as hydro, solar, wind, wave and biomass energy. These renewable energy resources are alternative energy that have not been optimally used. The lack of the reserve energy resources that results dependence of energy supply from other areas should receive special attention from DIY government. To meet the energy demand, it is required to develop energy resources. Due to the development of energy resources requires long time and high cost, it is necessary to make energy planning well supported by energy policy. The purpose of this study is to identify the renewable energy potential of DIY and renewable energy infrastructure that has been built by the government. In addition, knowing DIY energy balance and energy forecasting up to 2025. Thus, the number of renewable energy mix to the non-renewable energy comsumption will be known. The results of this study indicate that in 2012, renewable energy potential of DIY is as follows